Identification of a novel mutation in ZAP70 and prenatal diagnosis in a Turkish family with severe combined immunodeficiency disorder - AYDINER, ELİF (ELSEVIER SCIENCE BV, 2013)
Protein tyrosine kinases (PTKs) play an important role in T cell development and activation. In vitro and in vivo defects, resulting in variable deficiencies in thymic development and in T cell antigen receptor (TCR) signal transduction, in PTKs have been shown. ZAP70, one of those PTKs, is a 70-kDa tyrosine phosphoprotein and associates with the chain zeta and undergoes tyrosine phosphorylation following TCR stimulation. It is expressed in T and natural killer (NK) cells. Several mutations were shown to lead to an autosomal recessive form of severe combined immunodeficiency disease (SCID). Here, we present a family with a novel mutation in ZAP70. The proband, the second child of the first cousin parents of Turkish origin, was diagnosed with SCID having R514C mutation on homozygous state. She had decreased CD8(+) T and natural killer cells, normal CD4(+) T cells, high serum Ig E level, perivascular dermatitis and ichthyosis. This article presents clinical features of a novel mutation on ZAP70 and the first prenatal molecular diagnosis of ZAP70 deficiency. Different mutations in ZAP70 and related phenotypes reported in the literature are also discussed. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Novel mutation; ZAP70; SCID; Prenatal diagnosis; ZAP-70-DEFICIENT PATIENTS; TYROSINE KINASE; T-CELLS; ZAP-70; SYK; DEFICIENCY; SELECTION; HUMANS; CHAIN; MICE